Angela Merkel's Leadership in Germany's Open Door Policy Regarding the Handling of the Refugee Crisis in Europe - Muhamad Dasep (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2024)
This research will examine Angela Merkel's leadership in the Open Door Policy to address the refugee crisis that occurred in Europe in 2015. The conflict in Syria led people there to seek refuge in other countries, culminating in a significant increase in refugee waves worldwide. Europe, due to its geographical proximity to the Middle East, became the most affected region in receiving these refugees. In response, Germany, under Chancellor Angela Merkel, decided to open its borders to refugees from Syria. Unlike other European Union countries that chose not to accept refugees, Germany took a different approach. However, this policy faced opposition domestically from the AFD opposition party and the anti-Islam PEGIDA movement. Using the concept of leadership, this paper seeks to answer the question: How did Angela Merkel's leadership in Germany's Open Door Policy contribute to addressing the refugee crisis in Europe? This research utilizes secondary data collection methods, including books, journals, and documentation.